Where, how, who? Some questions for restorative justice. Issue 3 (13th July 2015) - Smyth and Gareth Jones, Graham; Edwards, Phil
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyse the settings, mechanisms and beneficiaries of restorative justice, querying whether a single procedure can have the wide-ranging benefits – to victims, offenders and the broader community – which have been attributed to restorative justice. Design/methodology/approach – The paper assesses the claims made for restorative justice in the light of contemporary British experience, taking evidence from the published evaluations of three Home Office-funded restorative justice schemes (Shapland et al., 2004, 2006a, 2007, 2008). Findings – It is found that ideas of community have played little part in restorative justice practice in Britain, but that restorative justice may benefit both victims and offenders. Given the differing needs of the two groups, it is suggested that this may be conditional on the prior articulation of relationships of interdependency – which in turn may strengthen informal communities. Originality/value – This paper clarifies the distinct benefits offered by restorative justice to victims and offenders, and reconceptualises the relationship between successful restorative justice practice and informal community relationships.